Impact of sustainability measures in the specialty coffee supply chain on the end consumer - Hopp, Jasmin-Maria (2017)
Specialty coffee stakeholders are pursuing sustainability measures in the supply chain in order to counteract the severe negative effects of the coffee industry with regard to the threats posed on the environment, fair trade, human rights and wildlife. This study is focusing on the impact sustainability measures have on the end consumer. In order to develop recommendations, the study explores connections between the willingness to pay a premium price and sustainability, the existing knowledge of consumers about ethical industry practices and ways to improve the communication of measures. The empirical research is based on focus group interviews. The study has shown that the first step is to raise awareness and educate the consumers about industry problems. Furthermore, the clear link between specialty coffee quality and sustainable practices needs to be communicated effectively. In order to increase the impact on the consumer, the delivery method and correct timing are crucial. The research findings were worked into recommendations which can be used by companies.